Vampires, Narcissists, and Psychopaths: The Psychopolitics of Stigma in Self-Help Books - Bogdan Vukomanović (Etnoantropološki Problemi)
Until now, self-help literature has been viewed as a medium through which the processes of neoliberalization took place at the "micro-level", i.e. at the level of individual consciousness. The central idea of ​​that set of research papers is that books in this field aim to internalize the "neoliberal self", that is, a depoliticized individual solely focused on self-improvement. Although this paper does not dispute the aforementioned conclusions, I believe that the previous studies of self-help literature have been focused on the prescribed construction of the relationship that an individual should have with themselves, at the expense of the relationship that an individual should establish with others. In other words, the focus of the previous analyzes was the cultivation of a desirable, positively valorized, socially acceptable personality. The aim of this paper is to focus on the "other side of the coin", that is, the production of those forms of subjectivity whose influence or mere presence the "successful neoliberal self" should avoid. The focus is directed toward what the self-help literature refers to as "emotional vampires", "toxic" people, "psychopaths" and "narcissists", as well as the advice on how to avoid them, deal with them or how to "heal" them. Through the analysis of self-help books dealing with these personality types, I aim to highlight that the construction of the neoliberal self also includes the marginalization, exclusion and stigmatization of undesirable forms of subjectivity, thus influencing the creation of certain forms of sociality as an integral part of its psychopolitics. This has significant implications for the possibilities available to other forms of sociality, which are also a subject of examination.